Family Commitments and Career Success: Earnings of Male and Female Managers - Cannings, Kathy (Relations industrielles / Industrial Relations, 1991)
The dual-career family, with its attendant pressures for dual commitment to the home and to the career, has become an increasingly important phenomenon in recent decades. A firm-level data set is used to examine the impact of family commitments as well as cognitive, behavioral, and organizational factors on the earnings of 519 married middle managers in a large Canadian corporation. Alongside a number of behavioral variables as well as the functional division of managerial labor in the company, division of labor in the employee's household has a significant impact on managerial earnings. The inclusion of a variable reflecting the household division of labor in the managerial earnings function helps to explain a substantial proportion of the earnings disadvantage of women in this company that might otherwise simply be attributed to gender.
Keywords: Behavior; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Commitments; Dual career couples; Dual career family; Earnings; Labor Unions; Salaries pensions etc; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Statistical analysis; Studies; Variables; Women